Some representations on the feminine aspect in driving motor vehicles in the city of Morelia during the decades of 1960 and 1980 (Tzintzun, Revista de Estudios Históricos, 2021)
The present work is an invitation to go deep into seeing some of the main representations there were on women driving motor vehicles in the city of Morelia in the second half of the 20th century. It will specifically talk about several press releases and pictures from this period to help us understand what perceptions there were on this practice and its actors, and at the same time, there will be reflections on the case of the first female taxi driver in the city.
Keywords: representation; feminine; motor vehicles; stereotype; Morelia